Uma abordagem para migração automática de código no contexto do desenvolvimento orientado a modelos - Possatto, Marcos Antonio (Universidade Federal de São Carlos, 2013)
Code generators play a key role in model-driven software development. They are responsible for transforming high-level assets (models) into implementation assets (code). Most generators are based on templates, which are pieces of text instrumented with code expansion elements. They receive an input and produce an output according to the template's programming. To build such template-based generators, the code of an existing implementation, already tested and validated, can be used as a reference, in a process known as code migration. With software evolution and the need for changes in the code generator, the templates start to differ from this reference implementation. In order to restablish the synchronization, additional effort is required. Tackling the challenge of keeping these assets synchronized (reference implementation and templates) is this dissertation's subject. The goal is to provide some automation to the code migration process, even if partial, in order to increase productivity in the maintenance of code generators. A mechanism was developed to make it possible to automatically reproduce changes that are performed in the reference implementation into one or more code generation templates. This mechanism was evaluated through an empirical study, yielding good performance in a controlled environment. This indicates that automation can help to reduce the effort in the maintenance of code generators in a model-driven development context.
Keywords: Engenharia de software; Engenharia ida-e-volta; Geração de código; Implementação; Desenvolvimento orientado a modelos; Geração de código baseada em templates; Implementação de referência; Migração de código; Model-driven development; Round-trip engineering; Template-based code generation; Reference implementation; Code migration; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO